Exploring Academic Integrity in Online Assessment: Perspectives from EFL Teachers - Yola Savitri; Pupung Purnawarman (Journey: Journal of English Language and Pedagogy, 2024)
Four years have passed since the pandemic situation forced us to adapt in order to continue our education. This adaptation extends to the way we administer learning evaluations through the online assessment. Certain schools and universities continue to utilize these adaptations in education to this day. Furthermore, the online assessment raises several issues, one of which is the academic integrity. Thus, this paper explores the issue of academic integrity in online assessment from the perspective of EFL teachers. This study explores the teachers' views of academic integrity in online assessments, their experiences with academic integrity violations, and approaches to administering academic integrity. This study employed a survey method, using an online questionnaire distributed to EFL teachers across Indonesia and involving forty-two participants. The data collected from the questionnaire was analyzed using descriptive statistics to interpret the findings and draw conclusions. The results show that most teachers acknowledge the principle and significance of academic integrity, but they admit to having difficulties administering and monitoring academic integrity in their class. Furthermore, not all teachers are able to effectively manage their experiences with academic integrity violations. Therefore, further study considering this issue is suggested.